Caseworkers’ participation in procurement: Infrastructuring Child Welfare Services in Norway - Dahl-Jørgensen, Tangni C.; Parmiggiani, Elena (Computer supported cooperative work, 2023)
Procurement is a widely adopted collaborative approach for acquiring new systems in the public sector. It exemplifies a situation in which the early stages of digital system design define the boundaries and constraints of a new system that must be specified in the tender document (i.e., a binding offer). Researchers and government officials have long recognized the benefit of end-user participation in system design. Given the central role of the pre-tender phases in procurement processes, however, there is a need to better understand what affects user participation in such early stages. In this paper, we research a procurement process in municipal Child Welfare Services in Norway. We focus on caseworkers' participation in procuring a future case management system. We build on the concept of participatory infrastructuring to characterize how the meaning of participation was shaped through three overarching participatory infrastructuring practices of decision-making within a rigid procurement process: (i) scaling up the project, (ii) negotiating participation in meetings with potential suppliers and in tender documents, and (iii) positioning caseworkers as subject experts. The analysis of these practices reveals that the definition of user needs in the tender documentation and the creation of knotworks define both the boundary conditions and the modalities of participation. We contribute to the conversation on participatory infrastructuring in Computer-Supported Cooperative Work by discussing how participatory infrastructuring provides a conceptual understanding of participation in the context of municipal systems procurement.